Perceptions and Experiences of Change in Practices of Masculinity among University-Educated Men of Iranian Origin in Quebec - Zohreh Mehdizadeh (European Scientific Journal, ESJ, 2021)
Through 19 qualitative interviews with university-educated men of Iranian origin living in the province of Quebec, this article sets out to examine their perceptions and experiences of performing masculinity in a new social setting. The Life Course theoretical approach has been applied to analyze how a shift in the social, cultural, and family context run by different ideals of manhood impacts the practices through which men expressed their masculinity. Thematic and comprehensive analyses of the data revealed gender roles apportioned to men in the society of origin, conjugality, and legal standards of the host society to be the main domains where changes and challenges were experienced. The results help us understand that masculinity, like femininity, is a contextually situated trajectory constructed in an ongoing interaction between the larger social structures and individual agency; like any other pathways of individuals’ lives, masculinity is a continuous process of rethinking and reinventing certain configurations, including the gender relevant attitudes and behaviors establishing what manhood is about and how it should be in a given societal context (Carpenter, 2010; West & Zimmerman, 1987). Masculinity is also a situated act as it evolves in a sociocultural context that has already defined some expressions of gender identities as ideal (West & Zimmerman, 1987).